Comparison of spontaneous sensory recovery of noninnervated anteromedial thigh flap, latissimus dorsi flap, and gracilis muscle flap in lower extremity reconstruction: A prospective comparative study. Issue 4 (29th November 2018) - Rothenberger, Jens; Ramms, Eva Maria; Medved, Fabian; Kolbenschlag, Jonas; Daigeler, Adrien; Held, Manuel
Abstract : Background: We evaluated the time course and differences in the sensory recovery of three commonly used free flaps for lower extremity reconstruction. Furthermore, the sensory recovery of skin‐grafted muscle and skin paddle in latissimus dorsi flaps (LDMF) were differentiated. Methods: In a prospective study, 26 patients who had undergone free flap lower extremity reconstruction were enrolled. Among them, 9 received LDMF, 9 received gracilis muscle flaps (GMF), and 8 received anterior lateral thigh flaps (ALTF). The sensory recovery was investigated by using the Semmes–Weinstein test (SWT) at 6 and 12 months after the surgery. Results: All flaps recorded spontaneous sensory recovery. The GMF showed the smallest anesthetic area after 12 months as compared with the ALTF and LDMF (1 ± 3% vs. 18 ± 39% ( p < .05) vs. 35 ± 35% (p < .05), respectively). Qualitatively, ALTF exhibited the best sensory recovery with the lowest SWT values (ALTF 4.57 ± 1.12 vs. GMF 5.01 ± 0.81 8 [ p < .05], vs. LDMF 5.84 ± 0.52 [ p < .05]). The sensory recovery of skin‐grafted muscle was superior to that of the skin paddle in the LDMF (anesthetic area 29 ± 36% vs. 54 ± 33% [ p < .05], SWT 5.85 ± 0.60 vs. 6.30 ± 0.18 [ p < .05], respectively). Conclusion: All flaps displayed spontaneous sensory recovery potential over the investigation period, which appeared to be influenced by the flap type and size. The LDMF skin paddle showed lower potential for sensory recovery as compared with the skin‐grafted muscle area of the same flap. The GMF demonstrated a near‐complete sensory recovery after 12 months.